PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS DAN KOMISARIS INDEPENDEN TERHADAP AGRESIVITAS PAJAK PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2012-2014) - Lativa Ningrum, 12.05.52.0224; Wahjudi, Djoko (Students' Journal of Accounting and Banking, 2016)
This study aims to determine the effect of Liquidity, Leverage, Profitability and the Independent Commissioner of Tax Agresiveness Company at manufacture companies which listed in the Indonesia Stock Exchange. The population on this research is all manufacture company in the Indonesia Stock Exchange in 2012 - 2014. The sampling technique used was purposive sampling. The analytical tool was used is Multiple Regression Analysis Partial results of this study show the leverage of significant positive effect on tax agresiveness while variable liquidity, profitability and the independent commissioner doesn’t affect the tax agresiveness.Keywords: Liquidity, Leverage, Profitability, Independent Comissioner, Tax Agresiveness